Is diabetes a marker of higher risk after carotid revascularization? Experience from a single centre - Casana, R; Malloggi, C; Odero, A; Bulbulia, R; Halliday, AW (SAGE Publications, 2018)
Purpose: This single centre study investigates the influence of diabetes mellitus on outcomes following carotid artery endarterectomy or stenting. Methods: In total, 752 carotid revascularizations (58.2% carotid artery stenting and 41.8% carotid endarterectomy) were performed in 221 (29.4%) patients with diabetes and 532 (70.6%) patients without diabetes. The study outcomes were death, disabling and non-disabling stroke, transient ischaemic attack and restenosis within 36 months after the procedure. Results: Patients with diabetes had higher periprocedural risk of any stroke or death (3.6% diabetes vs 0.6% no diabetes; p < 0.05), transient ischaemic attack (1.8% diabetes vs 0.2% no diabetes; p > 0.05) and restenosis (2.7% diabetes vs 0.6% no diabetes; p < 0.05). During long-term follow-up, there were no significant differences in Kaplan–Meier estimates of freedom from death, any stroke and transient ischaemic attack, between people with and without diabetes for each carotid artery stenting and carotid endarterectomy subgroup. Patients with diabetes showed higher rates of restenosis during follow-up than patients without diabetes (36-months estimate risk of restenosis: 21.2% diabetes vs 12.5% no diabetes; p < 0.05). Conclusion: The presence of diabetes was associated with increased periprocedural risk, but no further additional risk emerged during longer term follow-up. Restenosis rates were higher among patients with diabetes.